2019
DOI: 10.1111/ijsa.12241
|View full text |Cite
|
Sign up to set email alerts
|

Work ethic and organizational commitment as conditions of unethical pro‐organizational behavior: Do engaged workers break the ethical rules?

Abstract: Unethical pro‐organizational behaviors (UPB) are actions that break rules or established standards, but are undertaken for the purposes of helping the organization or coworkers. Although research has already examined the role of work ethic and organizational commitment in shaping employee behaviors, little is known about the reason for and antecedents of employees undertaking UPB. In a sample of 425 working adults from multiple industries, we tested whether work ethic and organizational commitment dimensions p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 45 publications
(71 reference statements)
0
29
0
3
Order By: Relevance
“…Continuance commitment, which is similar to work engagement, also increases employee involvement in UPB [75]. The results of other studies indicate that normative commitment and affective commitment are predictors of unethical pro-organizational behavior [76].…”
Section: Work Engagement and Unethical Pro-organizational Behaviormentioning
confidence: 72%
“…Continuance commitment, which is similar to work engagement, also increases employee involvement in UPB [75]. The results of other studies indicate that normative commitment and affective commitment are predictors of unethical pro-organizational behavior [76].…”
Section: Work Engagement and Unethical Pro-organizational Behaviormentioning
confidence: 72%
“…The inset of Figure 4 a shows a periodically repeated photoisomerization confirming reliable hysteresis cycles for PEO-BDK-MR composite thin films with a slight distinctive-loss. The first-order kinetics of photoisomerization can be further understood by computing the photoisomerization rate and the thermal/optical activation barrier trans-cis photoisomerization Equation (1) [ 37 , 38 ]. The average value of of the PEO-BDK-MR polymer composite thin film is plotted versus the time ( t ), as shown in Figure 4 b.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the cis-isomers return to the trans-state either by cis-trans photoisomerization with a quantum yield ϕ CT or by thermal relaxation characterized by a rate k. The whole process is entirely described by σ T and σ C absorption cross-sections for the transand cisforms, respectively, as illustrated in Figure 2. To obtain a deeper insight into the kinetics of photoisomerization of the AZO molecule, photoisomerization rate and thermal/optical activation barrier for trans-cis photoisomerization is evaluated [37,38]. The photoionization rate (p) can be given as:…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, studies on the antecedents of UPB have confirmed many individual-level factors, including organizational identification [7], work passion [8], psychological entitlement [9], job insecurity [10,11], job satisfaction [12], moral disengagement [7], and organizational commitment [13]. In addition, leadership factors include transformational [14] and ethical leadership [15].…”
Section: Introductionmentioning
confidence: 99%